International Arctic cooperation in the era of global instability: Challenges and prospects - V. N. Konyshev; M. L. Lagutina; A. A. Sergunin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2025)
The Arctic, which has long been regarded as a region free from international conflicts and contradictions, is gradually becoming an arena of interstate rivalry. At the same time, even the ‘Ukrainian crisis’ of 2014 and the beginning of the special military operation did not completely cancel the mutually beneficial cooperation present in the region. This article identifies potential areas for con- tinuing and possibly deepening the constructive dialogue in the Arctic. In this regard, this article examines the latest trends in interstate cooperation in such areas as international legal regime, interaction in the fields of energy, transport logistics and scientific research, as well as elaboration of an adequate climate strategy and environmental monitoring in the Arctic. The authors conclude that although the destructive position of the ‘collective West’ toward Russia in the Arctic in recent years has created many problems for the development of fruitful international cooperation in the region and has largely devalued the concept of ‘Arctic exceptionalism’, opportunities for restoring constructive dialogue in all the areas considered remain. Science diplomacy could play a special role in this process. At the same time, the authors state that this dialogue will develop under new conditions: two hardly overlapping spheres of international cooperation in the Arctic are emerging. One of them encompasses interactions between the countries of the ‘collective West’, crystallizing around the ‘core’ represented by the United States and NATO, while the second centers around relations between Russia and friendly Asian countries (China, Vietnam, India, UAE), and the number of these countries may increase in the future.